2021
DOI: 10.1186/s12884-021-04269-4
|View full text |Cite
|
Sign up to set email alerts
|

Anemia among pregnant women in internally displaced camps in Mogadishu, Somalia: a cross-sectional study on prevalence, severity and associated risk factors

Abstract: Background Anemia in pregnancy is a serious global public health problem in most developing countries and a major cause of maternal morbidity and mortality. Somalia which already had very high maternal mortality ratio of 829 per 100,000 live births, pregnant women in internally displaced camps (IDPs) remain at most exposed. The aim of the study was to determine the prevalence, severity and associated risk factors of anemia among pregnant women in internally displaced camps in Mogadishu, Somalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
4
7
2
Order By: Relevance
“…In a study conducted in one of Mogadishu's internally displaced camps, the prevalence of anemia in pregnant patients was 44.4% and more than 50% of these participants never visited antenatal care. 20 In our study, the maternal mortality rate was 12.7%, which is similar to a previous study conducted in Ethiopia 14 and almost another report from Pakistan that observed a maternal mortality rate of 15%. 19 Using ANC package on a timely and frequent basis allows the delivery of essential services such as identification and management obstetric complications such as preeclampsia, tetanus toxoid immunization, intermittent preventive treatment for malaria during pregnancy (IPTp), and identification and management of infections such as HIV, syphilis, and other sexually transmitted infections (STIs).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In a study conducted in one of Mogadishu's internally displaced camps, the prevalence of anemia in pregnant patients was 44.4% and more than 50% of these participants never visited antenatal care. 20 In our study, the maternal mortality rate was 12.7%, which is similar to a previous study conducted in Ethiopia 14 and almost another report from Pakistan that observed a maternal mortality rate of 15%. 19 Using ANC package on a timely and frequent basis allows the delivery of essential services such as identification and management obstetric complications such as preeclampsia, tetanus toxoid immunization, intermittent preventive treatment for malaria during pregnancy (IPTp), and identification and management of infections such as HIV, syphilis, and other sexually transmitted infections (STIs).…”
supporting
confidence: 91%
“…In a study conducted in one of Mogadishu’s internally displaced camps, the prevalence of anemia in pregnant patients was 44.4% and more than 50% of these participants never visited antenatal care. 20 …”
Section: Discussionmentioning
confidence: 99%
“…This is relatively agreed with those of Nigerian and Kenyan studies related to second and third trimester. [1,6]. While the Malaysian study disagreed with this study regarding first trimester (65.4%) and second trimester (45.0%).…”
Section: Discussioncontrasting
confidence: 64%
“…In this study anemia among pregnant women in their first antenatal care visit is 56.9%, which is corresponding to some other studies of anemia prevalence done in Erbil city (55.5%) in 2013 [15], in Jordan accounts (56.7%) in 2012, [20], in Malaysia was (57.4%) in 2012 [19]. Anemic prevalence in pregnant reported in Nigeria (40.4%) in 2007 [1], while was lower in Kenya (36.2%) in 2012 [6]. The prevalence of anemia in pregnancy is low USA and Europe, were it accounts (24.1% and 25.1%) in 2003.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation